The secret life of Amanda K. Woods - Cameron, Ann 1943- (New York Puffin Books 1998.)
Living in a rural community in Wisconsin during the 1950s, eleven-year-old Amanda gradually and painfully learns a lot about herself, her parents, and her older sister.
Keywords: Self-perception -- Fiction; Mothers and daughters -- Fiction; Sisters -- Fiction; Family life -- Wisconsin -- Fiction; Wisconsin -- Fiction